PERAN KEPERCAYAAN PEMEDIASI AKSESIBILITAS DAN MEDIA SOSIAL TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN PADA OBJEK WISATA DEPATI COFFEE - Liantifa, Melifia; Agustin, Bela (Jurnal Ekonomi Sakti, 2025)
The problem formulation in this research is whether there is an influence of accessibility and social media on the decision to visit with trust as an intervening variable at the Depati Coffee Sungai Penuh tourist attraction? The aim of this research is to determine the influence of accessibility and social media on the decision to visit with trust as an intervening variable at the Depati Coffee Sungai Penuh tourist attraction. The analysis used in this research is descriptive quantitative with a path analysis approach. The research object is visitors to the Depati Coffee Sungai Penuh tourist attraction. The results of the research explain that there is a significant positive influence between accessibility on purchasing decisions, there is a significant positive influence between social media on purchasing decisions, there is a significant positive influence between trust on purchasing decisions. The accessibility variable has a significant positive effect on trust. Social media variables have a significant positive effect on trust. Furthermore, there is a significant positive influence between accessibility on the decision to visit through trust as an intervening variable to Depati Coffee Sungai Penuh. Then there is a significant positive influence between social media on the decision to visit through trust as an intervening variable to Depati Coffee Sungai Penuh. .